Design of Digital Information Media for the Situ Rawa Gede Tourism Destination, Bekasi City - Muhammad Syahri Fadhil; Sunarto; Mochamad Candra Wirawan Arief; Fanny Kristiadhi; Ahmad Prawira Dhahiyat (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This study aims to design a digital information medium in the form of a QR Code-based e-booklet as a means of delivering tourism information for the Situ Rawa Gede destination in Bekasi City. Method: The research employed a descriptive approach consisting of three stages: identifying tourists’ information needs, designing the media using Canva and Heyzine Flipbook, and testing its effectiveness among users. Data were collected through field observations, interviews with tourism managers, and questionnaires distributed to 30 tourist respondents. Result: The findings show that the designed e-booklet effectively presents tourism information interactively, efficiently, and is easily accessible through QR Code scanning. The effectiveness test yielded an average score of 4.53 in the “Excellent” category, indicating improved understanding and satisfaction among visitors. Contribution: This study contributes to the development of digital promotional media for local tourism destinations by introducing a QR Code-based model that is practical and sustainable. The findings also provide insights for tourism managers seeking to implement innovative and user-friendly digital media to enhance visitor engagement and support community-based tourism promotion.